Aplicación de la filosofía LEAN en la construcción del centro comercial Zona Centro. - Picado-Marchena, Luis Fernando (Instituto Tecnológico de Costa Rica, 2015)
This project aims to optimize the use of financial, human , material and financial resources in the construction of Zona Centro Mall made by EDIFICAR company, applying the LEAN philosophy. A review of information pertaining to the company on planning and productivity aspects was performed. Also, the tools used by the company for control of these aspects were applied during the execution of this construction project. Last Planner tool is used for planning control and Activities Information System, work sampling and five minutes rating are used for productivity measurement and then a comparison between the results obtained through these techniques application is made. Also, an interview was done and it was focused on workers productivity during job time, in order to identify improvements in this aspect. Applying the techniques and tools mentioned in this work, in result, improvement opportunities were identified on construction processes.This paper concludes that using techniques of productivity measuring and tools for planning control is possible to build projects based on LEAN philosophy of continuous process improvement and resources optimization.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2015.
Keywords: Productividad; Planeación; LEAN; Mejora; SINA